RISK FACTORS OF THE DEVELOPMENT OF PRENOSOLOGICAL FORMS OF POSTPARTUM PYOINFLAMMATORY DISEASES - A.E. AGAREV; M.S. KOVALENKO; T.D. ZDOLNIK (Avicenna Tajik State Medical University, 2019)
Objective: Identification of risk factors of the development of prenosological forms of postpartum pyoinflammatory diseases. Methods: Main and control groups have been formed to identify risk factors. The мain group includes 181 women with complications of the postnatal period (subinvolution of the uterus, lohiometer). The control group was formed by mechanical selection of each fiftieth history of the birth of patients without the above-mentioned complications, its number was 303 people. The work is a retrospective study of the type of «case-control». Results: The following risk factors for the development of prenosological forms of postpartum pyoinflammatory diseases have been identified: unregistered marriage; irregular visits to antenatal clinic during pregnancy; beginning of sexual activity until the age of 18; lack of education; prenatal hospitalization for more than 1 day; preeclampsia during pregnancy; placental disorders during pregnancy; first birth; preeclampsia in childbirth; hydramnios; failure to progress; birth stimulation; С-section; emergency C-section; deep rupture of the vaginal mucosa; anemia; separation stays of mother and child. Conclusion: Most of the identified risk factors are related to the course of pregnancy and childbirth.